Thrypticus atomus Frey 1915 ... - Ovsyannikova, E. I.; Grichanov, I. Ya. (Zenodo, 2020)
Thrypticus atomus Frey, 1915 MATERIAL EXAMINED. Batetskiy dist., 1♀, Shchepy, 58.670°N, 30.122°W, 13.07.2020. DISTRIBUTION. Type locality: Finland: Karislojo. Austria, Belgium, Czech Republic, Finland, Hungary, Latvia, Netherlands, Russia (Arkhangelsk, Leningrad, Pskov, Ryazan, Yakutia, Krasnoyarsk), Sweden. New for Novgorod Region. ... : Published as part of Ovsyannikova, E. I. & Grichanov, I. Ya., 2020, Dolichopodidae (Diptera) fauna of the Novgorod Region. Addition, pp. 307-314 in Russian Entomological Journal 29 (3) on page 313, DOI: 10.15298/rusentj.29.3.12, http://zenodo.org/record/13166296 ...